TMS 2017 146th Annual Meeting & Exhibition Supplemental Proceedings - TMS, The Minerals, Metals & Materials Society (Springer International Publishing : Imprint: Springer, 2017)
This collection features papers presented at the 146th Annual Meeting & Exhibition of The Minerals, Metals & Materials Society.
Keywords: Materials science.; Engineering -- Materials.; Metals.; elektronické knihy; electronic books